Science and Society - What is Scientists' return to the Society: Round Table of the DOBA Business School, Maribor, 9. 12. 2015 - Ovin, Rasto (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
After almost 25 years of independence it is high time to assess the the universities' top researches' contribution to a better every day living of the home population. The promotion system is heavily concentrated on publishing top research abroad. Here absent is the mission of top researchers to perform as a members of a society thus enabling minimum return of investment by the society.Therefore the DOBA Business School had on December 12th 2015 organized a round table: Science and Society – What is Scientists' return to the Society? Participants at the round table were:• Peter Gabrijelčič, Dean, Faculty of Architecture, University of Ljubljana,• Dr. Lea Bregar, DOBA Business School,• Dr. Boris Cizelj, DOBA Business School and Slovenian Innovation Hub Ljubljana,• Jasna Dominko Baloh, Director of the DOBA Group,• Andrej Fištravec, Mayor of City of Maribor,• Dr. Alojz Križman, Former Rector of the University of Maribor and Former Mayor of City of Maribor,• Anton Habjanič, Director of TehnoCenter at the University in Maribor,• Dr. Željko Knez, Faculty of Chemistry and Chemical Technology at the University of Maribor,• Slavka Marinič, CEO, Primat d.o.o.,• Dušan Merc, prof., Headmaster of Prule Elementary School Ljubljana,• Dr. Rasto Ovin, Dean of the DOBA Business School,• Miro Puhek, DOBA Business School, Maribor• Dr. Ludvik Toplak, Director of the Alma Mater Europea and Former Rector of the University of Maribor, and• Ddr. Ana Vovk Korže, Faculty of Phylosophy, University of Maribor.